PENERAPAN WHATSAPP SEBAGAI MEDIA PEMBELAJARAN BAHASA ARAB PADA MATERI QIRAAH SISWA DI MTS MUHAMMADIYAH MANDALLE KABUPATEN GOWA - Nurhudayah S (Universitas Islam Negeri Alauddin Makassar, 2023)
This jurnal discusses the application of WhatsApp as a medium of Learning Arabic on the material of students at MTs Muhammadiyah Mandalle Gowa Regency. This study aims (1). To find out the design of WhatsApp learning as a medium of learning Arabic on the material of students in class IX A (2). To find out the use of WhatsApp as a medium of learning Arabic in the material of students in class IX A (3). To find out the effectiveness of WhatsApp as a medium of learning Arabic on students' qiraah material, (4). To find out the supporting factors and inhibiting factors of WhatsApp as a medium of learning Arabic on students' qiraah material. This research is qualitative research. Data is collected using observations, interviews and documentation. Data is collected and then processed in 3 ways, namely: data reduction, presentation of data and withdrawal of conclusions. The results of the study that the application of WhatsApp as a medium of Learning Arabic in the material of students at MTs Muhammadiyah Mandalle went well. Learning design compiled by teachers is made with analysis of student characteristics including learning objectives, learning materials, methods used, assessment and evaluation of students. Effectiveness is seen from achieving learning goals, the ability of teachers and students to use WhatsApp, effective in the use of time and cost. Supporting factors in the application of WhatsApp as a learning medium are teachers, parents of students, the availability of smartphones, and good networks and WhatsApp is flexible. And the inhibiting factor in the application of WhatsApp as a learning medium is not available internet data quotas, bad networks, replacing WhatsApp numbers and distracted concentration. The implications of such activities are expected: 1) In the implementation of Arabic learning on qiraah material can provide a change in attitude and behavior in students of class IX A MTs Muhammadiyah Mandalle in a better direction in relationships with fellow humans, the environment and God. 2) WhatsApp implementation forms for teachers and students can be optimized. 3) The obstacles faced become a lesson to continue to do and work in online learning using WhatsApp as a learning medium.